Factors Influencing Community Participation in Development Planning through Development Planning Forum (Musrenbang) in Sumbermanjing Wetan District Malang Regency - Sanjayani, Rita (FIA UB, 2016)
A good plan is needed as a guidance of development activity. Development planning forums (Musrenbang) which involve local community are held annually and in hierarchy from the lower level (Village) to higher level (National) in Indonesia. This research aims to determine the level and the factors influencing community participation in District Musrenbang. The method is quantitative by using Partial Least Square (PLS) analysis. The research finds that the community participation in Sumbermanjing Wetan District Musrenbang is in the fifth rung of Arstein’s Ladder of Participation namely placation. According to PLS analysis result, the factors influencing community participation in District Musrenbang are culture, educational level, income, perception, and communication.